9.2 – Adding & Subtracting Rational Expressions
Remember adding & subtracting fractions?
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator!
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ _
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ _ 3. 3 =
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ _ 3. 3 = 8 _
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ _ 3. 3 = 8 _ 9 =
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ _ 3. 3 = 8 _ 9 = _
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ _ 3. 3 = 8 _ 9 = _ –Same w/rational expressions!
Ex. 1 Simplify each expression
a ab a
Ex. 1 Simplify each expression a ab a = 6 + ab a ab
Ex. 1 Simplify each expression a ab a = 6 + 8(b) ab a ab a(b)
Ex. 1 Simplify each expression a ab a = 6 + 8(b) ab a ab a(b) = 6 + 8b ab ab
Ex. 1 Simplify each expression a ab a = 6 + 8(b) ab a ab a(b) = 6 + 8b ab ab = 6 + 8b ab
Ex. 1 Simplify each expression a ab a = 6 + 8(b) ab a ab a(b) = 6 + 8b ab ab = 6 + 8b ab
Ex. 1 Simplify each expression a ab a = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6
Ex. 1 Simplify each expression a ab a = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m
Ex. 1 Simplify each expression a ab a = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m (m+2)(m-2)
Ex. 1 Simplify each expression a ab a = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2)
Ex. 1 Simplify each expression a ab a = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2)
Ex. 1 Simplify each expression a ab a = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m 3(m+2)(m-2)
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2)
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2)
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2)
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2)
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4 3(m+2)(m–2)
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4 = m + 4 3(m+2)(m–2)
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4 = m + 4 _ 3(m+2)(m–2)